Gatekeeping in agriculture publications: agriculture editors' uses of information sources and channels - Talley, Rebecca Suzanne, author; O'Keefe, Garrett, advisor; Zimmerman, Don, committee member; Irlbeck, Nancy, committee member (Colorado State University. Libraries, 2010)
Agriculture producers have had a long-standing relationship with trade publications, turning to these sources for information that is used to make decisions in their production management, in turn affecting the entire multi-billion dollar industry in the United States. Editors of these trade publications act as gatekeepers of the information that is published, allowing information into the publication or excluding it. Ultimately, this has an impact on the information that reaches agriculture producers and has an overall affect on the agriculture industry. This study examined the criteria agriculture editors value in sources, those sources that are most used and most preferred and why, those channels that are most used and most preferred and why, and if a source' s channel use affects the use of that source' s information. Results indicated that agriculture editors put a high value on sources that provided accurate, unbiased information and were easily accessed. Due in part to these criteria, editors rated sources that are publicly funded higher than most of those that are privately funded as most used and most preferred sources. Editors also indicated that e-mail was the most used and preferred information channel due to ease and efficiency, with the majority feeling that the information channel a source delivered information through influenced the use of that source' s information. Findings from this study indicate that sources may be able to push information to agriculture editors, and ultimately to publication, by conforming to those criteria that editors value and by delivering information through their preferred information channels.
Keywords: Agricultural literature -- United States -- Decision making; Agriculture publishing -- United States -- Decision making; Agriculture -- Research -- United States